An evaluation of excellence in primary healthcare units after the introduction of a performance management innovation in two regional states of Ethiopia: a facility based comparative study - Wubishet Kebede Heyi; Elias Mamo Gurmamo; Amare Assefa Anara; Agegnehu Gebru Sendeku; Abera Refissa; Feyisa Serbessa Yadeta; Mesele Damte Argaw; Binyam Fekadu Desta (BMC Health Services Research, 2022)
Abstract Background The Ethiopian Ministry of Health strives to achieve universal health coverage (UHC) through increasing the number of its high-performing primary healthcare units. Although the Ethiopian health system is managed within a decentralized political system, the Ministry of Health works towards institutionalizing performance management innovations and organizational cultures that increase the excellence of primary healthcare entities. To date, there has been little evidence gathered on the factors influencing the excellence of primary healthcare units in Ethiopia. Therefore, the aim of this study was to assess and compare how the introduction of performance management and organizational culture innovations through project support affect the excellence of primary healthcare units in Ethiopia. Methods A facility-based comparative study was conducted in USAID Transform: Primary Health Care project supported and non-supported primary healthcare units located in the Oromia and Southern Nations Nationalities and Peoples’ (SNNP) regions of Ethiopia. Quantitative data were collected from randomly selected health workers using interviewer-administered questionnaires. In addition, primary healthcare unit excellence measurements were extracted from routine health information databases over eight quarters. The data were analyzed using the Statistical Package for Social Science (SPSS IBM v 20) research software package. Results were presented in frequency tables and graphs. After checking the data for homogeneous distribution, a paired sample t-test for equal variances, otherwise known as the Mann–Whitney U test was analyzed to claim statistically significant difference at P < 0.05. Results Out of 368 invited health workers, 364 participated in this study, (a response rate of 98.9%). Slightly higher than two-thirds of participants were enrolled from the Jimma Zone of Oromia Region. Orientations on performance management standards were provided to 101 (68.2%) and 45 (48.3%) health workers from project-supported and non-supported facilities, respectively. The mean perceived organizational culture score with [± Standard Deviation (SD)] was 3.72 ± 0.75 among project-supported health workers and 3.385 ± 0.75 among non-supported health workers, respectively. An independent sample t-test showed statistically significant differences, where project-supported health workers had higher mean scores on perceived organizational culture than their non-supported counterparts, with t = 433, df = 362, P = 0.001. The mean baseline primary healthcare unit excellence score was 63.2% and 50.5% for project-supported and non-supported health facilities, respectively. The end line excellence scores increased to 93.3% for project-supported and 79.1% for non-supported facilities. The end line overall primary healthcare units’ mean rank excellence scores were 257.67 for the project supported and 105.66 for non-project supported facilities. This result of a non-parametric test, i.e. the Mann–Whitney U test revealed that project-supported facilities were higher and had a positive statistically significant difference (U = 2,728, z = -13.78, P = 0.001). Conclusions The findings of this study underscore a direct relationship between implementing performance management innovations and enhancing organizational cultures for excellence at primary healthcare units. Project-supported primary healthcare units had higher organizational culture and excellence scores than their counterpart non-supported facilities. Therefore, achieving UHC through excellence in primary healthcare facilities requires scaling up of performance management innovation interventions.